PEMAKNAAN IDENTITAS PADA FENOMENA "KW VERSUS ORIGINAL" - Windhie Agita Divanti; Nurhadi Nurhadi; Pranawa Pranawa (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2021)
Shoes may not be just as essential as footwear. The meaning of shoes now cannot be seen from the needs alone; the purpose becomes integrated either as a basic need or a lifestyle that is even used as an identity. The existence of the production of KW shoes proves that using a particular brand is considered to be able to support one's appearance. Identity is more formed because it is created by representing how a person wants to be seen and the implied message he wants to convey from what he wears. This identity becomes vulnerable to changes, such as domination and minority, which causes the essence to change. Like someone who uses KW sneakers, they will be embarrassed if the original user catches them. This makes KW users belittled. The impact on the formation of a political identity where the sense of owning genuine sneakers will be able to elevate one's status that one will be considered excellent and well-off. But on the other hand, the users of KW shoes feel they have the same sense of belonging as the original users by making replicas of the actual shoes and want to be considered like the original shoe users.